SMSS J130522.47-293113.0: A high-latitude stellar X-ray source with pc-scale outflow relics? - Da Costa, G.; Soria, Roberto; Farrell, S.; Bayliss, D.; Bessell, M.; Vogt, F.; Zhou, G.; Points, S.; Beers, T.; López-Sanchez, A.; Bannister, K.; Bell, M.; et al. (Oxford University Press, 2018)
We report the discovery of an unusual stellar system SMSS J130522.47-293113.0. The optical spectrum is dominated by a blue continuum together with emission lines of hydrogen, neutral, and ionized helium, and the NIII, CIII blend at ~4640-4650 Å. The emission-line profiles vary in strength and position on time-scales as short as 1 d, while optical photometry reveals fluctuations of as much as ~0.2mag in g on time-scales as short as 10-15 min. The system is a weak X-ray source (f 0.3-10 = (1.2 ± 0.1) × 10 -13 ergs cm 2 s -1 in the 0.3-10 keV band) but is not detected at radio wavelengths (3s upper limit of 50 µJy at 5.5 GHz). The most intriguing property of the system, however, is the existence of two 'blobs', a few arcsec in size, that are symmetrically located 3'. 8 (2.2 pc for our preferred system distance of ~2 kpc) each side of the central object. The blobs are detected in optical and near-IR broad-band images but do not show any excess emission in Ha images. We discuss the interpretation of the system, suggesting that the central object is most likely a nova-like CV, and that the blobs are relics of a pc-scale accretion-powered collimated outflow.